2000
DOI: 10.1107/s0021889800001199
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel structure of reinforcing silica and carbon

Abstract: Using small‐angle x‐ray (SAXS), neutron (SANS), x‐ray diffraction and light scattering, we study the structure of colloidal silica and carbon on length scales from 4 Å < q−1 < 107 Å where q is the magnitude of the scattering vector. These materials consist of primary particles of the order of 100 Å, aggregated into micron‐sized aggregates that in turn are agglomerated into 100 µ agglomerates. The diffraction data show that the primary particles in precipitated silica are composed of highly defective amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 15 publications
2
80
1
Order By: Relevance
“…The fitting parameters of this model are the average radius of gyration of the primary particles p g R , , its fractal surface dimension of the primary particles d p , the average cluster radius of gyration cl g R , and its mass fractal dimension d cl . In addition, the four pre-factors H [1][2][3][4] are also free fitting parameters. As introduced here, these pre-factors have no distinct physical meaning, however the relationship H 1 = N p,B H 3 is often used in the literature, which serves for the estimation of the average number of particles per cluster, N p,B 19 .…”
Section: Unified Beaucage Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The fitting parameters of this model are the average radius of gyration of the primary particles p g R , , its fractal surface dimension of the primary particles d p , the average cluster radius of gyration cl g R , and its mass fractal dimension d cl . In addition, the four pre-factors H [1][2][3][4] are also free fitting parameters. As introduced here, these pre-factors have no distinct physical meaning, however the relationship H 1 = N p,B H 3 is often used in the literature, which serves for the estimation of the average number of particles per cluster, N p,B 19 .…”
Section: Unified Beaucage Modelmentioning
confidence: 99%
“…For automobile tires SBR rubbers are often reinforced by the addition of fillers such as carbon black or silica particles [1][2][3][4][5][6] . In particular, activated silica reinforcement plays an important role in improving the properties of the SBR compounds [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[72][73][74][75][76][77] Silica rubber systems also form hierarchical structures consisting of agglomerates, aggregates and particles and the size of each structure can be estimated from the scattering function. Moreover, we can estimate the size distribution of silica particles.…”
Section: Applicationsmentioning
confidence: 99%
“…Moreover, we can estimate the size distribution of silica particles. 74 Schaefer et al 76 investigated the hierarchical structures of the precipitated silica prepared by the acidification of water glass using light scattering, USAXS, SAXS and WAXS, which cover the range from 3 Â 10 À6 to 50 nm À1 , as shown in Figure 7. By fitting four levels of the unified Guinier/power-law equation to the scattering function at 3 Â 10 À6 oqo4 nm À1 , they found that the hierarchical structure consists of agglomerate level 2 (R g ¼ 115 mm, D m ¼ 1.9, mass fractal), agglomerate level 1 (R g ¼ 0.9 mm, D s ¼ 2.8, rough surface), aggregates (R g ¼ 66 nm, D m ¼ 1.8, mass fractal) and particles (R g ¼ 4.7 nm, D s ¼ 2 or Porod law, smooth surface).…”
Section: Applicationsmentioning
confidence: 99%